Financial instruments disclosure practices: evidence from Malaysian listed firms - Adznan, Syaimaa'; Puat Nelson, Sherliza (Elsevier, 2014)

(untitled)
The current changes in business settings have directed companies to conduct businesses at the international level which requires the use of financial instruments. The-mandatory MFRS 7, an adoption of IFRS 7 standard has been implemented for entities to disclose their involvement with financial instruments. Thus, the aimed of this study is to investigate the financial instruments disclosure practices (FID) among Malaysian listed companies; specifically, on the level of compliance with MFRS 7. The overall results indicate that companies complied with MFRS 7, though there are several requirements omitted by companies. Furthermore, with the revised of MCCG in 2012, this study examines the association of corporate governance mechanisms with the extent of FID among companies. Based on sample of 319 companies, result indicates that audit committee independence, internal audit independence (out-source) and audit fees are positive and significantly associated with FID. Hence, it suggests that effective corporate governance may have some influence on the extent of disclosure level among companies.